2004
DOI: 10.1098/rspb.2003.2656
|View full text |Cite
|
Sign up to set email alerts
|

Ecological conditions during winter affect sexual selection and breeding in a migratory bird

Abstract: Populations of migratory birds have undergone marked declines, although the causes and mechanisms remain unknown. Because environmental effects on population dynamics are mediated by the effects of ecological factors on individuals, understanding changes in individual phenotypes in response to ecological conditions is key to understanding population trends. We show that breeding individuals of a declining population of trans-Saharan migratory barn swallows, Hirundo rustica, were affected by environmental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 32 publications
4
148
0
4
Order By: Relevance
“…Our hypothesis is independent of these inconsistencies, however, since sexual selection on traits exhibiting environment-dependent phenotypic plasticity is not uncommon (e.g. Garant et al 2004;Saino et al 2004). Degree of change in arrival date could therefore have a sexually selected component (e.g.…”
Section: Bird Migration and Sexual Selection C N Spottiswoode And Omentioning
confidence: 92%
“…Our hypothesis is independent of these inconsistencies, however, since sexual selection on traits exhibiting environment-dependent phenotypic plasticity is not uncommon (e.g. Garant et al 2004;Saino et al 2004). Degree of change in arrival date could therefore have a sexually selected component (e.g.…”
Section: Bird Migration and Sexual Selection C N Spottiswoode And Omentioning
confidence: 92%
“…Barn swallows (Hirundo rustica) are colonial nesting passerines that breed throughout Europe and winter in sub-Saharan Africa. Saino et al (2004) reported the relationship between reproduction and primary productivity on the wintering grounds (measured by normalized difference vegetation index; NDVI). They found that a difference in G2 s.d.…”
Section: Estimating Carry-over Effectsmentioning
confidence: 99%
“…Much of this interest is based on the clear recognition that factors occurring at one period of the annual cycle can influence events occurring at another [3][4][5][6][7]. Such seasonal interactions can reveal ultimate fitness consequences of the choice of wintering and stopover locations made by birds that travel to breed.…”
Section: Introductionmentioning
confidence: 99%